AGRESIVITAS DAN VIOLENSIA - Simorangkir, Hieronymus (Universitas Katolik Santo Thomas Sumatera Utara, 2002)
There is a number of distinctions regarding the nature of aggression and its function. Therefore it is necessary to elucidate clear differences between the active engagement in gaining mastery over the environment for survivalâs sake, and self defence with force when threatened, and enjoyment of torturing, controlling, or killing without provocation or real need. Of these explanations it would elucidatively appear that aggression and violence differ, but both interact one another.